2018
DOI: 10.4103/1319-2442.225201
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of chronic kidney disease in Cote D'Ivoire: An analytic study conducted in the department of internal medicine

Abstract: Chronic kidney disease (CKD) has become a public health problem because of its increasing prevalence. The objective of this study was to describe the current profile of CKD in our working conditions. This is a descriptive retrospective study of patients admitted for CKD during the period from January 2010 to December 2014 in the Internal Medicine Department of the university hospital of Treichville in Abidjan. CKD was defined by a glomerular filtration rate below 60 mL/min lasting for at least three months. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…The probable etiologies of CKD were dominated by CGN with 70.91% of cases. Our results corroborate with those of the numerous studies that show a high proportion of CGN in the aetiologies of especially in our context [14].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The probable etiologies of CKD were dominated by CGN with 70.91% of cases. Our results corroborate with those of the numerous studies that show a high proportion of CGN in the aetiologies of especially in our context [14].…”
Section: Resultssupporting
confidence: 93%
“…Fayrouz Zemed et al observed hypertension in 46% of cases in Morocco in 2017 [13]. In our context, hypertension followed by HIV infection is the two main risk factors for chronic renal failure [14].…”
Section: Resultsmentioning
confidence: 58%
“…Sakhuja et al [15] reported that about twothirds of their patients had developed ESRD at the time of the first consultation with a nephrologist. Similarly, a Cote D'Ivoire study involving 252 patients reported that nine out of ten patients were at ESRD at presentation [16]. This report is in agreement with findings by other researchers where majority of patients were seen at advanced stage of CKD due to several reasons including silent and asymptomatic nature of CKD, lack of population awareness, poorly equipped and high cost of health system [11,[17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 84%
“…Research has demonstrated increasing prevalence of hypertension with age. The risk of hypertension related complications such as cardiovascular disease and CKD is equally heightened among the older adults [14,16,21,[25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…In the West, DN is the leading cause of dialysis. In sub-Saharan Africa in general, it is the second leading cause after hypertension, but the third leading cause in Côte d'Ivoire after hypertension and HIV infection (10). In our practice, hospital data show that diabetic kidney disease is at the stage of end-stage chronic kidney disease (ESCKD) at the time of diagnosis in one-third of cases.…”
Section: Introductionmentioning
confidence: 66%